Structures of monomeric and oligomeric forms of the Toxoplasma gondii perforin-like protein 1 - Ni, T; Williams, S; Rezelj, S; Anderluh, G; Harlos, K; Stansfeld, P; Gilbert, R (American Association for the Advancement of Science, 2018)
Copyright © 2018 The Authors, some rights reserved. Toxoplasma and Plasmodium are the parasitic agents of toxoplasmosis and malaria, respectively, and use perforinlike proteins (PLPs) to invade host organisms and complete their life cycles. The Toxoplasma gondii PLP1 (TgPLP1) is required for efficient exit from parasitophorous vacuoles in which proliferation occurs. We report structures of the membrane attack complex/perforin (MACPF) and Apicomplexan PLP C-terminal b-pleated sheet (APCb) domains of TgPLP1. The MACPF domain forms hexameric assemblies, with ring and helix geometries, and the APCb domain has a novel b-prism fold joined to the MACPF domain by a short linker. Molecular dynamics simulations suggest that the helical MACPF oligomer preserves a biologically important interface, whereas the APCb domain binds preferentially through a hydrophobic loop to membrane phosphatidylethanolamine, enhanced by the additional presence of inositol phosphate lipids. This mode of membrane binding is supported by site-directed mutagenesis data from a liposome-based assay. Together, these structural and biophysical findings provide insights into the molecular mechanism of membrane targeting by TgPLP1.